Construction Effective Knowledge Integration Strategy Based on Culture Algorithm Framework - Chen, Si-hua (2010 International Conference of Information Science and Management Engineering, 2010)
Integrating knowledge from different subjects and sources to obtain an effective knowledge base is the key to improve decision quality and enhance organizational core competency. We put forward a knowledge integration strategy under the framework of culture algorithm. It encodes the knowledge uniformly and through the evolvement of the two phases of population space and belief space the communication protocol is established among the two spaces. Then an effective and concise knowledge base is automatically produced. The experiment shows that comparing with traditional genetic algorithm, the model can classify the knowledge more precisely, reduce redundant knowledge and remove contradictory knowledge.